Mathematical Model for One Year Planning of a Manufactory - S.A. Fahad, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper is an attempt to help the manager of a manufactory toplan for the next year by a scientific approach, to maximize the profit and Ø¢ provide optimal Ø¢ monthly quantities of Ø¢ production, Ø¢ inventory,work-force, prices and sales. The computer programming helps us to execute that huge number of calculations.